Effect of selective transcranial direct current stimulation on dorsal and ventral pathways of reading - Bhattacharjee, Sagarika (Nanyang Technological University, 2022)
Transcranial direct current stimulation (tDCS) can modulate reading which is processed by dorsal (sub-lexical) and ventral (lexical) pathways. The dorsal route comprises the inferior parietal lobule, superior temporal gyrus, and inferior frontal gyrus and is involved in grapheme-to-phoneme conversion. The ventral route (lexical) comprising of left middle temporal gyrus, basal temporal area, and inferior frontal gyrus is involved in semantic access. Previous studies have reported inconsistent findings in tDCS to modulate the reading performance. This could be due to (1) the route (dorsal and ventral) specific tDCS was not applied, (2) reading tasks did not involve either lexical or sub-lexical processing, and (3) the variability in tDCS outcome due to sex (male versus female) was not considered. Study 1 developed a computational framework named Systematic Approach for tDCS Analysis (SATA) to derive two optimal montages with minimal overlap in the current spread. Two montages of electrode size of 5 × 5 cm2 and current intensity of 2mA were selected with- (1) anode at CP5 and the cathode at CZ to target the inferior parietal lobule of dorsal pathway, and (2) anode at TP7 and cathode at the nape-of-the-neck, targeting middle/inferior temporal gyrus of ventral pathway. In Study 2, two experiments were conducted using these montages from study 1 to investigate the effects of tDCS on two types of reading tasks- (1) regular, irregular, and pseudo-word reading in English, and (2) real word reading in Chinese and English. In Experiment 1- 18 proficient English readers were recruited, and anodal tDCS was applied across three separate dorsal, ventral, and sham sessions. Participants were asked to read word lists containing the regular, irregular, and pseudo-words immediately after tDCS. Results show that stimulation of both dorsal and ventral pathways enhanced regular word reading but failed to modulate pseudo-word reading. Ventral pathway stimulation did not modulate irregular word reading. This could be related to the high proficiency of the participants in English which facilitated the utilization of the ventral pathway to a maximal level, thereby leaving no room for further improvement. Surprisingly, dorsal pathway stimulation slowed down both regular and irregular reading. The increase in reaction time could be explained by the conflict between the pronunciations generated by the two pathways. Overall, the findings suggested that interaction between the dorsal and ventral route determines the behavioral outcome for readers proficient in one language. Bilingual word readers are expected to independently utilize either of the pathways, depending on the orthographic depth and level of proficiency in each language. Thus, Experiment 2 investigated the effect of tDCS on Chinese-English bilinguals by following the similar protocol of experiment 1. Sixteen proficient bilinguals were asked to read word lists in both the languages pre- and post-stimulation. Results show that dorsal pathway stimulation facilitates reading in both languages, whereas ventral pathway stimulation only enhances Chinese reading. Failure to modulate English reading by ventral pathway stimulation could be due to higher exposure and usage of the language. Higher the script-specific sub-lexical proficiency in each language lower was the effect of dorsal pathway stimulation. In general, a common reading network was supported for bilinguals. Interestingly in both experiments in Study 2, a significant sex difference was observed with males showing higher stimulation benefits. Naturally, two questions arose- (1) whether the observed sex difference in tDCS is due to the higher current intensity being received at the target region of interest (ROI) by males compared to females? And (2) what factors related to the cortical anatomy contribute to such differences? Hence, a simulation-driven Study 3 was conducted on a large opensource dataset (n =240) by simulating current intensity maps using structural MRI images of males and females distributed equally across the young, middle, and older age group (age 18 to 88 years). The study estimated the relationship between the neuroanatomical factors (brain volumes, cerebral dimensions, and brain torque) and current intensity at target ROI. Results showed that- (1) the current intensity differed between males and females but is dependent on age, (2) cerebrospinal fluid volume is the most significant determinant, and (3) brain-torque plays a key role in mediating the sex difference in older age only. Findings from this study helped explain the experimental observations of Study 2 (young males received higher current intensity than females). The present thesis concludes that tDCS (1) can modulate reading behavior when tDCS and the functionality of the underlying neural route are tuned together, (2) the effect depends on the degree of involvement of a pathway and reading proficiency, and (3) the effect is mediated by sex which is associated with the underlying neuroanatomical variation.